Hypertension in Pregnancy: A Nested Case-Control Study - Noor Hidayah; Oktia Woro Kasmini Handayani; Ari Yuniastuti; Dina Nur Anggraini Ningrum (Universitas Negeri Semarang in collaboration with Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI Tingkat Pusat) and Jejaring Nasional Pendidikan Kesehatan (JNPK), 2025)
Hypertension during pregnancy is the leading cause of maternal and neonatal morbidity and mortality. In Indonesia, 30 % of deaths are caused by hypertension. This study was conducted to analyze the risk factors for hypertension in pregnancy in mothers with high pregnancy risk. A nested case-control study design was employed, with data sourced from secondary records of obstetric medical documents from Gondosari Health Centre, Kudus Regency, Central Java Province, Indonesia, for the years 2021, 2022, and 2023. The number of hypertension cases was 46, and the number of controls was 92. The technique for collecting case data was based on reviewing the medical records of mothers with hypertension. In contrast, control data was taken by random sampling from mothers with high risk but who did not have hypertension. Statistical analysis used the chi-square (bivariate) and logistic regression (multivariate) tests. The study’s results stated that significant factors for hypertension in pregnancy were gestational age of 20 weeks, obesity, and primigravida with p 0.037, p 0.044, and p 0.010. Pregnant women > 20 weeks have a risk of 2.267 times to experience pregnancy hypertension, obesity has a risk of 4.288 times to experience hypertension in pregnancy, and non-primigravida status is at a higher risk of hypertension in pregnancy than primigravida mothers by 0.252 times. Mothers who have these three factors together have a probability of 80.79% of experiencing hypertension during pregnancy. This study concluded that gestational age > 20 weeks, obesity, and non-primigravida were related to the risk of hypertension in pregnancy at the study site; mothers who had gestational conditions > 20 weeks, obesity, and non-primigravida had the highest likelihood of developing hypertension in pregnancy.